Differences in Maxillary and Mandibular Premolar Length Distortion at Various Angulation Angles of Periapical Radiographs - Erwin Setyawan; Dyah Triswari; Sari S A (Denta Journal Kedokteran Gigi, 2024)
Background: Periapical radiographic techniques are usually used in root canal treatment. Distortion on bisecting technique periapical radiographs is relatively more common, especially on premolars located at the curved jaw area. Objective: To determine the difference in the length distortion of the maxillary and mandibular premolars at various exposure angles of periapical radiographs. Methods: The research conducted using observational analytic research, and the research design is cross-sectional. The sample used in this study were 30 upper premolars X-rayed using the periapical bisecting technique with a reference angle from the first literature book +30 and a reference angle from the second literature book +40 and 30 lower premolars X-rayed at -10 and -15 angles. Results: On the independent sample T-test, p value<0.05 for both the upper and lower premolars, so it can be concluded that there is a significant difference in distortion with a reference angle of +30 and +40 on upper premolars and -10 and -15 reference angles on the lower premolars. Discussion: Distortion of periapical radiographs with bisecting technique occurs more easily. The placement of the periapical sensor must be as close as possible to the object so that the correct position of the periapical sensor also plays a role in the formation of distortion. Conclusion: There is a significant difference in the length distortion of the upper and lower premolars on the angle of exposure periapical bisecting radiographs from the two reference books.